INFORMASI VAKSIN DI MEDIA SOSIAL DAN PROGRAM VAKSIN COVID-19: LANGKAH APA YANG DAPAT DILAKUKAN OLEH PEMERINTAH REPUBLIK INDONESIA? - Era Purike; Astriana Baiti (Cross-border, 2021)
The use of social media today has become one of the vital needs both in society and institutions. The public can easily access a variety of information through their technological devices. In 2019, social media users in Indonesia had reached 150 million users, and health information accessed by the public can shape diverse public opinions on vaccination programs. Research is needed to search the relationship between vaccine information available on social media that is accessed by the public with the attitude taken by the community towards the vaccination program and what steps can be taken by the government of the Republic of Indonesia to make it well-implemented. This study uses a qualitative method by using a literature review of several national and international journals relevant to the research topic. The results showed that the majority (43%) of the information available on the internet presented incorrect information about vaccines. Furthermore, it can be seen that the top 10 websites in the search engines show an anti-vaccine attitude. With many social media users in Indonesia and the lack of scientific sources that the public can access regarding vaccines, this dramatically affects people's attitudes towards vaccination programs. In addition, the small number of followers from all social media platforms owned by the government in disseminating information about the vaccination program. Three main factors can influence people's attitudes towards vaccines. The first is socio-cultural and demographic factors. The second factor is health communication, and the third factor is political conditions or distrust of the government. Therefore, it is necessary to take anticipatory steps from the government following these three factors so that the vaccination program would reach successful implementation.